Viral interference of the bacterial RNA metabolism machinery. Issue 1 (2nd January 2017) - Dendooven, Tom; Van den Bossche, An; Hendrix, Hanne; Ceyssens, Pieter-Jan; Voet, Marleen; Bandyra, K. J.; De Maeyer, Marc; Aertsen, Abram; Noben, Jean-Paul; Hardwick, Steven W.; Luisi, Ben F.; Lavigne, Rob
ABSTRACT: In a recent publication, we reported a unique interaction between a protein encoded by the giant myovirus phiKZ and the Pseudomonas aeruginosa RNA degradosome. Crystallography, site-directed mutagenesis and interactomics approaches revealed this 'degradosome interacting protein' or Dip, to adopt an 'open-claw' dimeric structure that presents acidic patches on its outer surface which hijack 2 conserved RNA binding sites on the scaffold domain of the RNase E component of the RNA degradosome. This interaction prevents substrate RNAs from being bound and degraded by the RNA degradosome during the virus infection cycle. In this commentary, we provide a perspective into the biological role of Dip, its structural analysis and its mysterious evolutionary origin, and we suggest some therapeutic and biotechnological applications of this distinctive viral protein.